The emperor's nightingale and other magical stories - Gallagher, Belinda (Miles Kelly Thaxted, 2012)
"The Emperor's Nightingale and Other Stories" is a collection of classic tales, including Hans Christian Andersen's famous story about a nightingale that sings beautifully. The book features themes of love, sacrifice, and the importance of art, with enchanting illustrations that bring each story to life. It aims to inspire and entertain young readers while imparting valuable life lessons through timeless narratives.